Durum wheat – crop cultivation strategies, importance and possible uses of grain - Wyzińska, Marta; Różewicz, Marcin (Polish Journal of Agronomy, 2021)
Durum wheat grains are in demand on the international market because they exhibit exceptional quality traits, which make them suitable for use in the pasta industry. Most Polish pasta producers import the necessary raw material from other countries (e.g. Italy). However, it is also possible to grow durum wheat under the conditions of Poland, as cultivars that can be successfully cultivated under these climatic conditions, as well as those that can overwinter successfully, have already been grown. When compared with the common wheat, durum wheat performs much better in terms of yellow pigments, gluten, glassiness and grain hardness. Under Poland’s conditions, it yields lower than common wheat, but the grain reaches a higher price. It should be stated that durum wheat is an important cereal, whose grain is used mainly for pasta and semolina production. The aim of this study is to characterise the method cultivation, cultivation possibilities, and usage of durum wheat grains.